Society, polity and land relations in Andhra Pradesh : a historical perspective - Sinha, Ajay (Mussoorie, 1996)
This monograph elaborately traces the origins of the Andhras as a race, later culminating in a territorial unit. It is a rich source of information on trials and tribulation of Andhra Pradesh from the earliest times to independence and after.
Keywords: Land reform Andhra Pradesh; IAS as an editor